Expression of Fluorescent Genes in Trypanosoma cruzi and Trypanosoma rangeli (Kinetoplastida: Trypanosomatidae): Its Application to Parasite-Vector Biology - Guevara, Palmira (2005)
Two Trypanosoma cruzi-derived cloning vectors, pTREX-n and pBs:CalB1/CUB01, were used to drive the expression of green fluorescent protein (GFP) and DsRed in Trypanosoma rangeli Tejera, 1920, and Trypanosoma cruzi Chagas, 1909, isolates, respectively. Regardless of the species, group, or strain, parasites harboring the transfected constructs as either episomes or stable chromosomal integrations showed high-level expression of fluorescent proteins. Tagged flagellates of both species were used to experimentally infect Rhodnius prolixus Stal, 1953. In infected bugs, single or mixed infections of T. cruzi and T. rangeli displayed the typical cycle of each species, with no apparent interspecies interactions. In addition, infection of kidney monkey cells (LLC-MK2) with GFP-T. cruzi showed that the parasite retained its fluorescent tag while carrying out its life cycle within cultured cells. The use of GFP-tagged parasites as a tool for biological studies in experimental hosts is discussed, as is the application of this method for copopulation studies of same-host parasites